PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA - Beatrix Tuto Sura Sura; Yuliana Tamu Ina Nuhamara; Erwin Randjawali (Program Studi PGSD Universitas Flores, 2024)
The low understanding of learning concepts among students in mathematics learning is caused by various factors, one of which is the lack of use of instructional media resulting in students being more passive. The purpose of this study is to explore the effects of implementing a learning model on students' understanding of mathematical concepts. The research method used is a quantitative approach with a one-group pre-test-post-test experimental design. The study population consists of all eighth-grade students at Anda Luri Catholic Junior High School, divided into four classes: VIII A (29 students), VIII B (30 students), VIII C (30 students), and VIII D (29 students). The subjects of this study are students from VIII C who underwent treatment using the instructional model. The research instrument used is a written test consisting of five essay questions. To evaluate the impact of the instructional model, an independent t-test was conducted. The analysis of the results shows a significant difference, thus supporting the alternative hypothesis while rejecting the null hypothesis. Therefore, it can be concluded that the use of the instructional model has a significant impact on the understanding of mathematical concepts among eighth-grade students, especially in the topic of systems of linear equations with two variables.